1997
DOI: 10.1002/(sici)1099-0836(199705)6:2<104::aid-bse102>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Environmental proactivism and firm performance: evidence from security analyst earnings forecasts

Abstract: There is an ongoing debate over the impact of corporate pro-environment actions and strategies (reflected, for example, in pollution prevention and emission reductions, product re-design, materials stewardship) on corporate financial performance in US corporations today. A review of the existing literature in this area yields no consistent pattern of relationships between corporate environmental proactivism and financial performance when historical corporate accounting performance and stock market measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(132 citation statements)
references
References 35 publications
6
125
1
Order By: Relevance
“…It stated that there would be an increase in corporate ROA and ROE after efforts to prevent pollution through emissions reduction within one to two years of initiation. A negative relationship between the emission index and financial performance was also found in studies by [23], [24]. However, our findings were consistent with those of a study by [26], where no significant relationship between emissions and financial performance was found.…”
Section: B Reliability Testsupporting
confidence: 93%
See 1 more Smart Citation
“…It stated that there would be an increase in corporate ROA and ROE after efforts to prevent pollution through emissions reduction within one to two years of initiation. A negative relationship between the emission index and financial performance was also found in studies by [23], [24]. However, our findings were consistent with those of a study by [26], where no significant relationship between emissions and financial performance was found.…”
Section: B Reliability Testsupporting
confidence: 93%
“…Reference [23] suggested that there is a negative link between environmental performance and financial performance. Their study focused on 13 firms in the US pulp and paper sector and used data from 1978.…”
Section: B Environmental Improvement and Financial Performancementioning
confidence: 99%
“…As we know, the type and the amount of the environmental protection investment must be approved by the government and the firm [53]. In addition, a higher growth rate indicates better environmental performance [54,55]. Thus, growth rate of environmental protection investment reflects environmental performance.…”
Section: Data Collection and Variables Definitionmentioning
confidence: 99%
“…The following studies reported negative relationships: Brammer et al (2006), Cordeiro and Sarkis (1997), Dobre et al (2015), Filbeck and Gorman (2004), Konar and Cohen (2001), Moore (2001), Cordeiro (2001), andLima Crisóstomo et al (2011). A main argument for the existence of negative relationship is that firms trying to enhance EP draw resources and management effort away from core areas of the business, resulting in lower profits.…”
Section: Background and Theory On Environmental Performance-firm Perfmentioning
confidence: 99%